Influence of iron, growth temperature and plasmids on siderophore production in Aeromonas hydrophila - Naidu, A.J.; Yadav, M. (Microbiology Society, 1997)
Aeromonas hydrophila strains obtained from diarrhoeal samples of human patients (19 isolates) and freshwater ponds (11 isolates) were analysed for siderophore production. Both clinical and environmental isolates showed significantly increased siderophore production under iron-limiting conditions both at 28 degrees C and at 37 degrees C. Clinical isolates consistently produced higher levels of siderophores than did the environmental isolates. The role of plasmids in moderating siderophore production was studied after curing with acridine orange. Treatment with acridine orange for 24 h removed the larger plasmids but the smaller plasmids (< 5 MDa), more common in the environmental isolates, were resistant to curing. As found in the untreated isolates, the cured clinical isolates produced higher mean levels of siderophores than the cured environmental isolates. Siderophore production in A. hydrophila was significantly influenced by iron-limiting cultural conditions and the source of isolates, but plasmid content and growth temperature at 28 degrees C or 37 degrees C had little effect on production. The basis for the greater production of siderophores in clinical isolates than in environmental isolates needs further study.